Identification of Pollen Characteristics as Apis cerana Feed Sources in Honeycomb, in Serang Purbalingga - Vanesa Yolanda; Sukarsa Sukarsa; Hexa Apriliana Hidayah (Fakultas Biologi Universitas Jenderal Soedirman, 2020)
Serang Purbalingga village is a fertile area and has the potential for the development of Apis cerana honeybee business. Honeybee products are known to have high economic value. The development of honeybee business will be better if supported by the avaibility of pollen from flowering plants as feed sources. Pollen that use to be A. cerana feed sources are taken from plants flower around the beehive and matched with pollen inside honeycomb. The purpose of this research is to determine the diversity and character of pollen from plants found around beehive and inside A. cerana honeycomb. This research conducted by descriptive survey method where the data obtained from field used as material for analysis and describing the characteristics of pollen found. Variable in this research is pollen characters with parameters are pollen units, size, shape, apertures and ornamentation. Based on results, there are 23 species of plants included in 17 families found around the beehive with varying of pollen shape, namely spheroidal, prolate-spheroidal, sub-prolate, and prolate. The smallest to largest pollen sizes are minutae, mediae, and magnae. Types of pollen ornamentations are rugulate, reticulate, echinate, psilate, scabrate, to baculate. Pollen apertures are varies monosulcate, monoporate, tricolporate, tricolpate, tetracolpate, hexacolpate to syncolpate. Pollen characters inside honeycomb are identical to 12 pollen of plant species found around the beehive where the pollen shape are spheroidal, prolate-spheroidal, sub-prolate and prolate. There are several types of ornamentation, namely reticulate, rugulate, echinate, psilate and sacbratte. Apertures are varies from monosulcate, monoporate, tricolporate, tricolpate to syncolpate. Key words : Apis cerana, characters,diversity, pollen, Purbalingga